Risk Management Approach in Solar Power Plant Projects Using the SLR Method - Agistin, Veriza; Whardani, Putri Nurul Kusuma; Nasution, Soraya Muthma Innah; Revolis, Messa; Sahti, Armia Lara (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Utilizing solar energy is among the renewable energy sources that are both abundant and kind to the environment. Therefore, the development of Solar Power Plants (PLTS) in Indonesia continues to grow as part of the clean energy transition and efforts to meet national renewable energy targets. However, solar power plant (PLTS) projects face various risks ranging from technical risks, resource risks, environmental risks, social and community risks, economic risks, occupational health and safety risks, to regulatory and legal risks that can hinder their success and efficiency in implementation, necessitating risk management. Structured risk management is crucial for ensuring that the solar power plant project can operate efficiently, safely, and sustainably. This research was conducted to identify the most significant risks in a solar power plant construction project using a qualitative method through a systematic literature review approach. Then, the findings from previous studies were synthesized to provide a comprehensive overview by identifying and classifying the main risks documented in the literature. This research aims to enhance the development of policies and risk management strategies for renewable energy initiatives in Indonesia